7y-35=-12y

Simple and best practice solution for 7y-35=-12y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7y-35=-12y equation:


Simplifying
7y + -35 = -12y

Reorder the terms:
-35 + 7y = -12y

Solving
-35 + 7y = -12y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '12y' to each side of the equation.
-35 + 7y + 12y = -12y + 12y

Combine like terms: 7y + 12y = 19y
-35 + 19y = -12y + 12y

Combine like terms: -12y + 12y = 0
-35 + 19y = 0

Add '35' to each side of the equation.
-35 + 35 + 19y = 0 + 35

Combine like terms: -35 + 35 = 0
0 + 19y = 0 + 35
19y = 0 + 35

Combine like terms: 0 + 35 = 35
19y = 35

Divide each side by '19'.
y = 1.842105263

Simplifying
y = 1.842105263

See similar equations:

| 1.2y-0.7y=3.5 | | -5(-7+x)-7x=x | | -6(w+1)-w-13=-7(w+5)+16 | | 20v^2+v=12 | | 9-W=-2 | | 11-3(x+5)=11 | | 0.4x+0.3x=2.1 | | y+.125=2y+.875 | | 4x+1=2(3.5-x) | | n+n+1+n+2+n+3+n+4=-65 | | 8.4x+91.02=-11.6x+89.36 | | -5.5y^2+275x-1394=1906 | | 8.4x+91.02=-11.6x+89.3 | | 4x+1=2(.3+2) | | -6x^2-19x-15=0 | | -[8z-(13z+10)]=10+(4z+0) | | 9x^3(y+5)-18x^2(-5-y)-6x(y+5)= | | 1.333p^2-1=0 | | 8.4x+910.2=-11.6x+89.36 | | 8(4.00+X)=72.00 | | y=50x^2+30000 | | 7.3x-1.4=5.9 | | y+2y-3(2y+6)=114 | | 8x-7y= | | .8333333333+.2t=.6666666667 | | -abs(x+3)-4=-14 | | 8x+5=36x | | -(z+9)+(4z+1)=-3(z+1) | | h=-16t^2+12t+40 | | 8b+-7=7b-2 | | c=50l^2+30000 | | 6(x-6)-8(x-2)=-16 |

Equations solver categories